Biomechanical evaluation of movement in sport and exercise the British Association of Sport and Exercise Sciences guide - Burden, Adrian (Adrian M.) (Routledge, Taylor & Francis Group, 2018)
Now in a fully updated and revised edition, this is still the only up-to-date, practical guide to the use of technology in sport and exercise biomechanics. it includes detailed explanations of the key theory underlying biomechanics testing and measurement, along with advice on choosing equipment and using it effectively. The second edition includes two completely new chapters on qualitative movement analysis and the assessment of movement coordination, and covers every key functional area in the biomechanics curriculum, including: motion analysis of force using video and on-line systems; measurement of force and pressure; measurement of torque and power using isokinetic dynamometry; electromyography; computational simulation and modelling of human movement; research methodologies; data processing